The Intellectual Dogmatism and its Relation to prejudice Among the Students of University of Anbar - Hamid Moussa, Elaf; Al-Kubaisi, Abdul Karim Obaid (Al-Adab Journal, 2020)
The present study aims to identify the level of intellectual dogmatism and prejudice, and to identify the type and degree of correlation between the intellectual dogmatism and prejudice variables among the students of University of Anbar. Also to identify the differences in intellectual dogmatism and prejudice due to gender variable (male - female) and the specialization variable (humanities and scientific). In order to achieve the aims of the study, the researchers have chosen a sample consisted of (400) students distributed to (6) faculties. 192 female students and 208 male students who represented the sample of designing the scale measures of intellectual dogmatism and prejudice. To achieve the aims of the study, 300 students have been chosen. The participants were distributed to four colleges, 144 female students and 156 male students. The researchers designed the intellectual dogmatism measurement scale, which consisted of (47) items in its final form. And the prejudice measurement scale which consisted of 48 items in its final from. Instruments' validity and reliability have been extracted. The findings of the study reveal the following :The participants have low level ofThere were no significance difference in the level prejudice due to the ( gender - scientific) and specialization variables at 0.05.Participants' Intellectual dogmatism degree is medium.There was significance difference (at 0.05) in the level of intellectual dogmatism according to the ( gender- specialization ) variables and for the favor of males and humanities .There is a statistically significant positive correlation at (0.05) between intellectual dogmatism and prejudice.